Education Policy in Rapid Education and Its Implementation in Educational Institutions: Kebijakan Pendidikan dalam Pendidikan Cepat dan Implementasinya di Lembaga Pendidikan - Syarifah, Syarifah; Sirojuddin, Akhmad (Halaqa: Islamic Education Journal, 2024)
For a really long time, Islamic life experience schools have been oppressed, both as far as acknowledgment and the situation with certificates that are not perceived by the state. understudies experience segregation in the working environment for a really long time. Moreover, pesantren are thought of as unfit to rival other regular instructive establishments at the institutional level, making it challenging to get the greatest government support. It is hoped that by conducting research using the library research method, a qualitative research approach, and naturalistic research methods, it will be possible to demonstrate that the existence of Law 18 of 2019 concerning Islamic Boarding Schools is an acknowledgment of the existence of Islamic boarding schools and their significant contribution to Indonesian education and teaching. Under Law 18 of 2019, the FKPM (Mu'Jadi Islamic Boarding School Communication Forum), which is a gathering forum for Asatidz, Kyai, and heads of Islamic boarding schools, was born out of the Islamic boarding school law. Modern Islamic Boarding Schools as well as Salaf Islamic Boarding Schools are among the members. Regulation 18 of 2019 also kills victimization graduate class of Islamic life experience schools in all lines of government and society. Keywords: Education, Police, Implementation